FEATURES OF BANKS’ INVESTMEMT OPERATIONS - A. V. Ramazanov (Russian Journal of Economics and Law)
The recent years are characterized by the increase of banks’ activity in the securities market. The article summarizes the author’s views on the commercial banks’ investment operations, and presents an analysis of banks’ activity during various operations at stock markets. The directions of investment activity development of the banks in Russia are shown.